1997
DOI: 10.1111/j.1752-1688.1997.tb03533.x
|View full text |Cite
|
Sign up to set email alerts
|

NUTRIENT MASS BALANCE FOR THE ALBEMARLE‐PAMLICO DRAINAGE BASIN, NORTH CAROLINA AND VIRGINIA, 19901

Abstract: A 1990 nitrogen and phosphorus mass balance calculated for eight National Stream Quality Accounting Network (NASQAN) basins in the Albemarle‐Pamlico Drainage Basin indicated the importance of agricultural nonpoint sources of nitrogen and phosphorus and watershed nitrogen retention and processing capabilities. Basin total nitrogen and phosphorus input estimates were calculated for atmospheric deposition (which averaged 27 percent of total nitrogen inputs and 22 percent of total phosphorus inputs); crop fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 11 publications
0
23
3
Order By: Relevance
“…In urbanized watersheds, point sources can account for greater than 60% of all phosphorus discharges (Nemery et al 2005). Point source discharges efficiently transfer phosphorus inputs to streams and P discharges can be greater than 25% of P inputs to streams in urbanized areas (McMahon and Woodside 1997). In the AlbemarlePamlico drainage basin, North Carolina and Virginia, it was estimated that even though permitted P point source inputs from waste water treatment plants and industry accounted for 16% of the P source inputs to the watershed, they accounted for greater than 40% of the stream loads (Spruill et al 1998).…”
Section: Trade Of Feed and Foodmentioning
confidence: 99%
“…In urbanized watersheds, point sources can account for greater than 60% of all phosphorus discharges (Nemery et al 2005). Point source discharges efficiently transfer phosphorus inputs to streams and P discharges can be greater than 25% of P inputs to streams in urbanized areas (McMahon and Woodside 1997). In the AlbemarlePamlico drainage basin, North Carolina and Virginia, it was estimated that even though permitted P point source inputs from waste water treatment plants and industry accounted for 16% of the P source inputs to the watershed, they accounted for greater than 40% of the stream loads (Spruill et al 1998).…”
Section: Trade Of Feed and Foodmentioning
confidence: 99%
“…Contributions of TN from atmospheric deposition were calculated as the sum of nitrate nitrogen and ammonium nitrogen wet deposition, nitrate nitrogen dry deposition, and developed-area wet and dry nitrate deposition, following procedures described in Sisterson (1990) and McMahon and Woodside (1997). Spatial data sets for atmospheric wet deposition of nitrate and ammonium nitrogen were overlain with reach catchment boundaries, and individual categories of nitrogen deposition were calculated and summed for each reach.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The focus of this collaboration is consistent with a strong recommendation in the National Research Council evaluation of NAWQA that models such as SPARROW be used both to generalize the information developed at a necessarily limited NAWQA sampling network, and to improve the understanding of mechanisms associated with the status and trends results from the first 10-year cycle of NAWQA (National Research Council, 2002). The North Carolina SPARROW effort extends the scope of mass balance work analysis completed during an earlier cycle of NAWQA (McMahon and Woodside, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In areas where ground water NO 3 -concentrations are at historically high levels, we may expect NO 3 -discharges to surface water to continue for many years unless there are mitigating biogeochemical processes along ground water flow paths. Consequently, it is important to understand the biogeochemical processes, such as denitrification, that may alter N concentrations in ground water systems.A number of recent studies have identified N sources and have presented mass-balance budgets at various scales (Correll et al, 1992;Jaworski et al, 1992;Barry et al, 1993;Puckett, 1995;Jordan and Weller, 1996;McMahon and Woodside, 1997). However, only one study (Hall and Risser, 1993) has shown a direct link to ground water NO 3 -concentrations.…”
mentioning
confidence: 99%
“…A number of recent studies have identified N sources and have presented mass-balance budgets at various scales (Correll et al, 1992;Jaworski et al, 1992;Barry et al, 1993;Puckett, 1995;Jordan and Weller, 1996;McMahon and Woodside, 1997). However, only one study (Hall and Risser, 1993) has shown a direct link to ground water NO 3 -concentrations.…”
mentioning
confidence: 99%